Clinical and histopathological characteristics of patients with incidental and nonincidental thyroid cancer - Krzysztof Kaliszewski (Archives of Medical Science, 2016)
Introduction: Thyroid nodules (TNs) are a common pathology. Their prevalence increases with age. Some of them are suspected of malignancy and qualified for surgery. Sometimes their malignant nature is detected incidentally after a surgical procedure. The aim of the study is to analyze clinical and histopathological characteristics of patients with incidental and nonincidental thyroid carcinoma (ITC vs. NITC). Material and methods: The case records of 3,241 patients with solitary and multiple TNs who were treated consecutively between 2008 and 2014 were analyzed retrospectively. After the final selection 235 (7.25%) patients were included in the study (202 females and 33 males, mean age: 52.9 +16.5 years). Seventy-five (31.91%) cases were incidentally diagnosed and 160 (68.09%) were diagnosed before surgery. Results : We did not observe any differences in age, gender or stage of disease at the time of diagnosis between the patients with ITC and NITC (p = 0.366, p = 0.850, p = 0.226 respectively). The occurrence of solitary nodules in patients with NITC was significantly higher compared to patients with ITC (p < 0.0001). There were no differences in histopathological types of thyroid cancer (TC). The logistic regression analysis showed that solitary TC was an independent predictor of NITC (p < 0.0001). Conclusions : There are no differences in gender, age or histopathological type of cancer in patients with ITC and NITC. Papillary TC is the predominant type in both groups. Incidence of TC in a solitary nodule is significantly higher in NITC than ITC. Solitary type of TC is an independent predictor of NITC. The prevalence of ITC is associated with multifocal type of TC.